Application of Cooperative Learning Model Student Teams Achievement Divisions (STAD) to Improve Children Ages 3-4 Years Speaking Ability in KB Cempaka Ngadipuro Village of Dukun District Magelang Regency - Diwanti, Dewik Retno; Adiarti, Wulan (BELIA: Early Childhood Education Papers, 2018)
The speaking ability for early childhood is very important for the provision of adulthood. At this time, children are easier to absorb stimuli received from the surrounding environment, therefore the speaking ability is very appropriate to be stimulated from an early age. One way that can be done to improve children's ability to speak is with new and enjoyable learning methods. Through the Student Team Achievement Division method, it is hoped that it can help children develop their speaking skills. This study aims to determine the differences in the increase in the speaking ability of children aged 3-4 years through the Student Team Achievement Division method at KB (Playgroup) Cempaka Ngadipuro District Dukun Magelang Regency. This research is a quantitative research using the One-Group Pretest-Posttest Design approach. The population is all students aged 3-4 years in the KB Cempaka Ngadipuro in Dukun District of Magelang Regency. The samples use are children aged 3-4 years in the all KB in Ngadipuro Dukun Magelang Regency as many as 30 children. The sampling technique is a Purposive Sample technique. The data collection technique uses the speaking ability scale of children aged 3-4 years, while the data analysis uses the Paired Sample t-Test and percentage techniques. Based on the results of calculation of hypothesis testing statistics obtain t-test data using the Paired Sample t-Test on the SPSS program obtain the value - t table > t count > t table, namely (-2.045> - 5,942 or 5,942> 2,045), Sig = 0,000 or Sig (2 Tailed) <0.05 so Ha is accepted and Ho is rejected. So, it can be concluded that there is a significant difference in the speaking ability of children aged 3-4 years in KB Cempaka Ngadipuro District Dukun Magelang Regency after the Student Team Achievement Division method is applied.